PENYULUHAN PENCEGAHAN DAN PEMBAGIAN LEAFLET HIV-AIDS PADA SISWA SMPN 3 PANGKAJENE PANGKEP - Suci Rahmadani; Balqis Nazaruddin; Rifka Zakilah Djafar; Dhea Rizky Andini; Chikita Alya Cahya Ningtyas; Ghariza Ariane; Nur Azizah Aini Fitratullah Yusuf; Nur Iftitah Ivan P (Gapenas Publisher, 2023)
Positive impact of health education can improve knowledge and attitudes, especially among adolescents who are vulnerable to HIV-AIDS transmission. To improve knowledge about HIV-AIDS, it is necessary to systematically integrate the material into formal and non-formal education, both in public and religious education. Based on primary data on the distribution of knowledge about HIV-AIDS in Mappasaile Village, Pangkajene District, Pangkep Regency, it is known that the community has low knowledge of HIV-AIDS, with only 0.7% having high knowledge and 99.3% having low knowledge. The research aims to improve the knowledge, understanding, and attitudes of adolescents in Mappasaile Village in preventing HIV-AIDS. The activity carried out was counseling using lecture and discussion methods and distributing brochures at SMPN 3 Pangkajene. The method used to evaluate the increase in adolescent knowledge during counseling activities is pre-test and post-test design. To analyze the data obtained, statistical testing is carried out using the Wilcoxon Match Pairs Test. The results show a significant increase in knowledge by 75.65%, and the counseling activities run according to plan and receive a positive response from the participants